Made & sold toys, t-shirts, prints, zines and other stuff - Jacquillat, Agathe; Vollauschek, Tomi. (London Laurence King Pub, 2009)
This book presents the most exciting self-initiated projects created by a new generation of graphic designers, illustrators and artists projects that are self-initiated, commercial and entrepreneurial.
Keywords: Commercial art; Graphic arts